PP87 Inpatient Drug Reimbursement: Approaches For A Democratic Process. (2019) - Wolf, Sarah; Wild, Claudia
Abstract : Introduction: In the context of limited healthcare resources and high healthcare expenditures, the introduction of new, cost-intensive medicines forces decision-makers to prioritize drug funding, especially in the areas of orphan diseases and oncology. In democratic societies, health policy decisions need to be evidence-based, transparent, fair, and efficient. Therefore, in some countries standardized (transparent) processes exist. In Austria, decisions on the reimbursement of new medicines have not been made for a long time. The aim of the present study was to develop different scenarios for a standardized, centralized reimbursement process for expensive hospital drugs in Austria that favors democratic decisions. Methods: A multi-stage approach was undertaken. Firstly, the reimbursement processes (only for original preparations) in Austria and other selected countries were investigated. Secondly, the strengths and weaknesses of these processes were analyzed based on predefined criteria, following the concepts of "accountability for reasonableness" (A4R) and "deliberative decision making". Thirdly, scenarios for an Austria-wide uniform reimbursement process for hospital drugs were developed. Results: Three scenarios were identified: (i) a reimbursement process for hospital drugs that follows the existing reimbursement process in the outpatient sector in Austria; (ii) a cooperative of decentralized Pharmaceutical and Therapeutics Committees for procurement, use, and reimbursement decisions for hospital drugs; and (iii) an adaptation of the existing reimbursement process of non-drug, highly specialized technologies to pharmaceutical interventions. Conclusions: According to the concepts of A4R and deliberative decision making, a transparent, evidence-based, fair, and efficient allocation of limited healthcare resources is indispensable for justifying decisions on health funding priorities in democracies. However, these criteria can be diametrically opposed. For example, methods, processes, and decisions can be evidence based, transparent, and fair, but also significantly more time consuming. Thus, a balance between the individual options for action is necessary, and priorities must be set.